Islamic Economics Study: The Effect of Exports, Foreign Investment, and Foreign Debt on Indonesia's Foreign Exchange Reserves - Hasanah, Surlidiya Nur; Noviarita, Heni; Setyanto, Alief Rakhman (Institut Agama Islam Negeri Kendari, 2025)
This study aims to examine the effect of oil and gas and non-oil and gas exports, foreign investment, and foreign debt on Indonesia's foreign exchange reserves from 1991 to 2024. This study uses a quantitative method with secondary data in the form of time series data and uses the Vector Error Correction Model (VECM) to identify the relationship between variables in the short and long term. The results show that, simultaneously, exports, foreign investment and foreign debt have a significant effect. Meanwhile, individually in the long term, oil and gas exports and non-oil and gas exports have a significant negative effect on foreign exchange reserves, while foreign investment has a significant positive effect and foreign debt has a significant negative effect on foreign exchange reserves. However, in the short term, the effects of oil and gas exports, foreign investment and foreign debt are not significant on Indonesia's foreign exchange reserves. This study integrates an Islamic economic perspective, emphasising the importance of the principles of justice, sustainability and the prohibition of usury in the management of macroeconomic variables related to foreign exchange reserves. These findings provide policy insights for sustainable foreign exchange reserve management, such as regulating foreign investment in accordance with sharia principles and carefully managing foreign debt to align with sharia values.